NGHIÊN CỨU HOÀN THIỆN CÔNG NGHỆ SẢN XUẤT GIOĂNG CAO SU ĐƯỜNG ỐNG XĂNG DẦU VN.PMT-100 - Lê, Anh Tuân; Nguyễn, Đức Nghĩa; Đỗ, Xuân Mạnh; Nguyễn, Hà Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE IMPROVEMENT OF PRODUCTION TEACHNOLOGY OF VN.PMT-100 RUBBER GASKETS FOR FUEL PIPELINESRubber gasket VN.PMT-100 is an important part of D100 fuel pipelines. These gaskets are spare parts and must be replaced after 5 years in standard storage conditions. In this paper, we present some results on improvement of prodution of the VN.PMT-100 gasket.The results show that the ingredients (nitrile rubber Krynac 4975F: 100; carbon black N330 Birla: 60; stearic acid: 3; zinc oxide: 7; TMTD: 0.2; DM: 0.3; TMQ: 0.5; paraffin: 1.5; sulfur: 2.0) and curing conditions (tem: 160oC; time: 15min; pressure: 16 MPa) are suitable to received products of high quality.